Awareness on Disability and Inclusive Education among the Prospective Teachers - Dheesha, Dr. J.B. (Voices of Teachers and Teacher Educators, 2020)
Inclusive education is a system of education wherein students with and without disability learn together and the system of teaching and learning is suitably adapted to meet the learning needs of different types of students with disabilities (Right to Persons with Disabilities Act (RPwD Act, 2016). The goal of inclusive education is to provide the most appropriate, equitable learning environment and opportunities to all students. This study focused on inclusive education for students with disabilities. The success of inclusive education is based on the attitude and acceptance of teachers and peer group. Teacher should have some knowledge about the different disability conditions and appropriate teaching methods in order to handle students with disabilities in the classroom environment. These skills and knowledge should be provided in their training programme itself. The study was an attempt to explore the awareness of prospective teachers on disability and inclusive education. 100 prospective teachers from ten B.Ed. Colleges situated in and around Coimbatore District, Tamil Nadu State were selected as samples. A questionnaire on the various aspects of disability and inclusive education was prepared by the researchers to collect the data. The results were discussed based the quantitative analysis. The finding shows that the Prospective teachers have very low awareness on disability and inclusive education.